Comparison of Molecular Iodine Spectral Properties at 514.7 and 532 nm Wavelengths - Hrabina J.; Acef O.; Burck F. du; Chiodo N.; Candela Y.; Sarbort M.; Hola M.; Lazar J. (Measurement Science Review, 2014)
We present results of investigation and comparison of spectral properties of molecular iodine transitions in the spectral region of 514.7 nm that are suitable for laser frequency stabilization and metrology of length. Eight Doppler-broadened transitions that were not studied in detail before were investigated with the help of frequency doubled Yb-doped fiber laser, and three of the most promising lines were studied in detail with prospect of using them in frequency stabilization of new laser standards. The spectral properties of hyperfine components (linewidths, signal-to-noise ratio) were compared with transitions that are well known and traditionally used for stabilization of frequency doubled Nd:YAG laser at the 532 nm region with the same molecular iodine absorption. The external frequency doubling arrangement with waveguide crystal and the Yb-doped fiber laser is also briefly described together with the observed effect of laser aging.